Penguatan Peran Ayah Dalam Mengatasi Fatherless Untuk Membentuk Psikologis Anak - Feby Inggriyani; Ari Darusalam; Ghilmi Sri Alfianti (Jurnal Medika: Medika, 2025)
The family is a place where individuals grow, develop, and learn the value that shape their personality. Children need guidance and direction from their parents as a foundation for fhe formation of their mental, thought, and behavioral patterns, which will remain with them throughout their lives. However, not all children grow up in ideal families. One form of family incompleteness is fatherlessness, a condution where a child loses a fther figur, either physically or emotioally. This can impact a child's psychological, social and academic aspects. This community service activity aims to provide education about the importance of a father;s role in a child's life through a workshop involving 20 partivipants. The methods used included material delivery, discuccions, educational games, parenting skill training, and experience-sharing sessions. Data were collected throught pre-tests and pos-tests. The result showed that the pre-test scores ranged from a minimum of 40,00 to a maximum of 72,00, with an average of 57,90. At the same time, the post-test score increased with a minimum score of 70,00 and maximum of 95.00, with an average of 83,10. The n-gain analysis showed an average index of 0,62, equivalent to 61,92%, which is in the moderate category. This finding indicate that the workshop signifivantly contributed to increasing participant's understanding of the issue of fatherlessness and teh urgency of father's roles in child development.